Estudio de factibilidad para la creación de un empresa dedicada a la producción y comercialización de cerveza artesanal en la ciudad de Armenia (Quindío). (2012)
This document will determine through a feasibility project, the creation of a company dedicated to the production and marketing of Artisan Beer in the city of Armenia. In this are the respective studies as they are the legal, market, technical, administrative, financial and environmental; which allow to know the concept of feasibility of the possible start-up of the company Bargo S.A.S, also: The legal study allowed to know the regulations and ordinances that regulate the production and commercialization of alcoholic beverages (artisanal beer) in the country and the different taxes that are handled at the regional level, as well as all the formalities necessary for the constitution of the company. Through the market study we analyzed the different variables that allow us to know the behavior of the beer market in the city of Armenia, the threats, opportunities, weaknesses and strengths that the company would have to put in place, our competitors, the possible demand for the product Handcrafted Beer and the price to be set. The technical study analyzed the different types of inputs and machinery necessary for the production of Artisan Beer, as well as a strategic location that allows the company to function well and recognize both its production plant and the PUB (bar) where the product will be marketed. It was found as a result of this study that it is necessary to purchase a microbrewery with a production capacity of 150 Liters plus four fermenters, in order to satisfy the demand. The administrative study describes the positions that should exist in the company and are expressed hierarchically in the organizational chart. Here, it also summarizes the monthly payroll that must be handled with their respective payloads and the parafiscal contributions that the company must make. In the financial study, the results of the previous studies are already taken into account in order to economically analyze the road of the project, starting with the initial investment of the project. This study identified the costs of manufacturing, the company's projections, its possible sources of financing, its break-even point, balance sheets, cash flows and the profitability of the project for investors. The environmental study allowed us to know the impact of the project on the environment and what care should be taken to conserve it.